1977
DOI: 10.1002/lary.5540870512
|View full text |Cite
|
Sign up to set email alerts
|

The applied anatomy of thyroglossal tract remnants

Abstract: Recurrences after surgery for thyroglossal cysts and fistulas were common until, in 1920, Sistrunk described his technique for removing the whole thyroglossal tract. Since that time there has been considerable argument concerning the exact path taken by the tract particularly in relation to the hyoid bone. In an attempt to elucidate this problem, studies have been made of embryos at varying stages of development, of serially step‐sectioned adult larynges and of surgical specimens. These studies suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
10

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(123 citation statements)
references
References 4 publications
1
112
0
10
Order By: Relevance
“…The exact incidence of thyroglossal duct remnants is unknown. Microscopic examination of 200 adult larynges reported by Ellis and van Nostrand showed thyroglossal duct remnants in 7 % of specimens [21], while an autopsy study involving 58 pediatric patients identified remnants of the thyroglossal duct or ectopic thyroid tissue in 41 % of cases [17]. Clinical manifestation of TGDC based on a mid-year mean patient population of 3,064,661 patients for Southern California Permanente Medical Group would correspond to 2.23/100,000 population at risk each year.…”
Section: Discussionmentioning
confidence: 91%
“…The exact incidence of thyroglossal duct remnants is unknown. Microscopic examination of 200 adult larynges reported by Ellis and van Nostrand showed thyroglossal duct remnants in 7 % of specimens [21], while an autopsy study involving 58 pediatric patients identified remnants of the thyroglossal duct or ectopic thyroid tissue in 41 % of cases [17]. Clinical manifestation of TGDC based on a mid-year mean patient population of 3,064,661 patients for Southern California Permanente Medical Group would correspond to 2.23/100,000 population at risk each year.…”
Section: Discussionmentioning
confidence: 91%
“…4 Cadaveric studies reveal persistent TGDC in 7% of the asymptomatic adult population. 5,6 TGDC may be found anywhere along the embryologic anlage, typically in close apposition to the hyoid bone and thyrohyoid membrane (approximately 60%-65%). 2,7 Enlargement of TGDC after an infection, or in the rare case of carcinoma within the cyst, is a well-documented phenomenon.…”
Section: Figmentioning
confidence: 99%
“…It obliterates completely by ninth week of gestation. Up to 60% cases of thyroglossal duct cyst (TGDC) show islands of functioning thyroid follicles in its wall [1]. However, parafollicular cells are absent.…”
Section: Introductionmentioning
confidence: 99%